Proposta de metodologia multicriterial para priorização de intervenção em ETEs segundo análise da vulnerabilidade socioambiental: estudo de caso em Fortaleza/CE - Magalhães, Antônio Marcelo Costa (2017)
There is a growing need to integrate decision-making techniques not only within private corporate environments, but also within the public administration environment. Increasingly, decisions that involve subjective factors are aided by a Decision Support System. Thus, from a scenario of several Sewage Treatment Stations (ETEs) that were known to present a history of non-conformities (of an environmental and operational nature), as well as being inserted in different social contexts of the same municipality, one evokes the objective of this research is to propose a multicriteria decision support methodology that generates an ordering in the prioritization of TEE intervention according to the integrative concept of relative socioenvironmental vulnerability associated to these stations. The proposed model was constructed based on the prescriptive paradigm, based on the perspective of several actors who work directly with the theme (specialist teachers, environmental authorities and staff of the local sanitation company) and applied in a case study in the city of Fortaleza considering 33 TEEs. The evaluation of the histories of the effluent samples collected, the on-site inspections in the TEEs and the regularly available sociodemographic data were tools used in the construction, as well as in the application and validation of the model. The PROMETHEE II overclassification method was used, with the intermediation of pseudocriteria (which compiled several criteria and value systems attributed by the decision makers in the elaboration). Visual PROMETHEE software was used as a facilitator of the calculations and as a visual resource for the results. The practicality of the research was achieved, given that the proposed methodology is based on criteria of facilitated reproducibility, provided that the premises of the adopted paradigm are safeguarded.